2016
DOI: 10.1021/acs.jafc.6b00951
|View full text |Cite
|
Sign up to set email alerts
|

Cucurbitacin E Potently Modulates the Activity of Encephalitogenic Cells

Abstract: Cucurbitacin E (CucE) is a highly oxidized steroid consisting of a tetracyclic triterpene. It is a member of a Cucurbitacin family of biomolecules that are predominantly found in Cucurbitaceae plants. CucE has already been identified as a potent anti-inflammatory compound. Here, its effects on CD4(+) T helper (Th) cells and macrophages, as the major encephalitogenic cells in the autoimmunity of the central nervous system, were investigated. Production of major pathogenic Th cell cytokines: interferon-gamma and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 44 publications
0
6
0
1
Order By: Relevance
“…Cucurbitacins are a family of natural products isolated from Cucurbitaceae plants, and possess a wide spectrum of pharmacological effects including anti-cancer, anti-diabetic, cytoprotective, and anti-inflammatory activities [15][16][17][18]. Cucurbitacin E (CuE), a highly oxygenated triterpene of cucurbitacins, is known to have a variety of pharmacological effects such as hepatoprotective, anti-inflammatory and anti-cancer activities [19][20][21][22][23][24]. Previous investigations have shown that CuE inhibits cell proliferation, migration, and invasion through different molecular mechanisms in vitro and in vivo, indicating that CuE exerts prominent investigation prospect in the treatment of various cancers.…”
Section: Introductionmentioning
confidence: 99%
“…Cucurbitacins are a family of natural products isolated from Cucurbitaceae plants, and possess a wide spectrum of pharmacological effects including anti-cancer, anti-diabetic, cytoprotective, and anti-inflammatory activities [15][16][17][18]. Cucurbitacin E (CuE), a highly oxygenated triterpene of cucurbitacins, is known to have a variety of pharmacological effects such as hepatoprotective, anti-inflammatory and anti-cancer activities [19][20][21][22][23][24]. Previous investigations have shown that CuE inhibits cell proliferation, migration, and invasion through different molecular mechanisms in vitro and in vivo, indicating that CuE exerts prominent investigation prospect in the treatment of various cancers.…”
Section: Introductionmentioning
confidence: 99%
“…Treatments of macrophage with pachymaran, TLR4, CD14, and CR3 led to the activation of p38 kinase. Activated p38 kinase then resulted in the activation of several transcription factors, which subsequently contributed to the control of inflammatory response. TLRs play an important role in both the innate immune system of the body and the acquired immune system, which is one of the current hotspots involved in the function of immune-regulating receptors. The major receptors that can combine with carbohydrate ligands are TLR2 and TLR4, and both of them have a close relationship with inflammation and immune regulation. , In this work, it was found that adding LPS to stimulate macrophages for 24 h significantly enhanced the expression of TLR2 and TLR4.…”
Section: Discussionmentioning
confidence: 99%
“…13 Recent our studies have reported that Cu E has an inhibitory effect on the proliferation of cancer cells. 14 However, it remains unclear whether Cu E inhibits the growth of cervical cancer cells.…”
Section: Introductionmentioning
confidence: 99%